(untitled) (Research, Society and Development, 2021)
Objective: to analyze, from the scientific literature, the role of home visits as a tool that promotes care in the Family Health Strategy. Methodology: A bibliographic study, of an integrative literature review type, carried out based on the online search for Brazilian scientific publications, in the following databases: Latin American and Caribbean Literature in Health Sciences (LILACS), Medical Literature Analysis and Retrieval System Online (MEDLINE), Bibliographic Database Specialized in Nursing (BDENF) and Scientific Electronic Library Online (SCIELO). The descriptors "Home Visit", "Nursing" and "Family Health Strategy" were used, all of them, mediated by the juxtaposition of the Boolean operator AND. In addition, the PRISMA flow chart was also used to demonstrate the process of identification, selection, eligibility and inclusion of studies. Results: It became evident that home visits are an essential tool for primary health care work that enables the organization of the FHS, through the insertion of health workers in family and community spaces. In addition, it is an activity guided by the principles of integrality, longitudinality, health promotion and continuity in the provision of assistance, and that these principles currently guide all assistance provided by ESF professionals. Final considerations: It is concluded that the VD aims to create and maintain the approximation of the users’ life context, enabling the appreciation of the subjective dimension of health practices, the experiences of users and health workers, and without any doubt, opens spaces for communication and dialogue between knowledge and practices.